Pengaruh leader member exchange terhadap organizational citizenship behavior dengan employee engagement sebagai pemediasi - Rizka Cintya Edwar; Sulastri Sulastri (Universitas Negeri Padang, 2020)
This research analyzed: (1) the influence of leader member exchange on Organizational Citizenship Behavior at PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur (2) the influence Leader member exchange on employee engagement at PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur (3) the influence of employee engagement on Organizational Citizenship Behavior at PT. Pelabuhan Indonesia II (Persero) Cabang Teluk (4) the influence of Leader Member Exchange on Organizational Citizenship Behavior through Employee Engagement at PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur. The study is causal research. The population were all non-managerial employees of PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur, totaling 101 people. The number of samples determined using Slovin collected samples obtained by 78 people taken using proportional cluster random sampling. Collecting data using a questionnaire with Likert scale. The analysis technique used is SEM use SmartPLS analysis. This research found that: (1) Leader Member Exchange has positive and significant effect on organizational citizenship behavior in PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur, (2) Leader Member Exchange has positive and significant effect on Employee Engagement in PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur, (3) Employee Engagement has positive and significant effect on organizational citizenship behavior in PT. Pelabuhan Indonesia II (Persero) Branch Teluk Bayur, (4) Employee Engagement has significantly mediate the relationship between Leader Member Exchange on organizational citizenship behavior in PT. Pelabuhan Indonesia II (Persero) Cabang Teluk Bayur.